UNDERSTANDING TERRORISM: AN ALTERNATIVE VIEW AND THE PAINFUL TRUTH: HOW POWERFUL NATIONS LEGITIMIZE TERRORISM - Antwi-Boasiako, Kwame B; Davis, Cindy P. (Journal of Terrorism Studies, 2022)
Despite human beings’ noble achievements on this planet including medicine, technology, physics, and chemistry, there is one characteristic of humans, which is disturbing and that act is “committing extreme cruelty and violence against its own species” (Smith 2007:41). This cruelty by human beings against themselves stems from many factors including power, ideology, religion, and terrorism. These categorizations, as Smith (2011) noted, are unfortunately used to dehumanize the other through societal definitions where one group, the powerful, sees itself as the paragons of civilization against the other, the weak, as barbarians. Terrorism, racism, ideology, and religion are but some of the variables nations have used and continue to employ to dehumanize others. By and large, powerful societies and nations regularly commit acts of terrorism yet there is the fear on the part of the weaker nations to openly accuse the former of their strategic atrocities. This paper attempts, through meta-analysis, to explain the ambiguities in defining terrorism and argues the painful truth is that powerful nations do utilize terrorism to advance their ideological, religious, and territorial acquisition ambitions while the small nations are blamed and accused as supporting terrorism for resisting the atrocities of the former.